The effects of plant growth regulators to Citrus suhuiensis callus induction - M. Fathil, Nur Alia; Mohamad Puad, Noor Illi; Amid, Azura; Azmi, Azlin Suhaida; Ibrahim, Rusli (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The diseases hampering Citrus suhuiensis (C. suhuiensis) or commonly known as ‘limau madu’ in East Asia has become a major problem to their cultivation and thus, plant cell culture techniques can be one of the solution to overcome this problem. Plant growth regulators (PGRs) play important role in inducing callus cultures and the correct types and concentration of PGRs will enhance and optimize the growth of callus. This paper investigated the effects of different types of cytokinins (2,4-D and NAA) and auxins (BAP and kinetin) as PGRs at the range of 0.5, 1.0, 2.0, 3.0 and 4.0 mg/L, respectively supplemented with MS media, 3% (w/v) sugar, 500 mg/L malt extract and 0.25% (w/v) agar under the continuous dark condition. The cotyledons from the seeds of C. suhuiensis were excised as the explant and the growth of callus at each treatment was measured as g/L of fresh weight and percentage of callus induction. It was found that 1.0 mg/L 2, 4-D gave the highest growth of callus (0.15g and 100% callus percentage). After identifying the effective PGRs, Central Composite Design (CCD) from Design Expert software version 7.0 was used obtain the optimum concentration of cytokinin and auxin on C. suhuiensis callus culture. Result showed that the highest amount of callus induced was 0.218g when using 1.0 mg/L 2,4-D and 1.0 mg/L kinetin.